Pandangan Hukum Islam terhadap Budaya Nyongkolan di Lombok - Jumatriadi, Jumatriadi (Lembaga Yasin AlSys, 2022)
This research was conducted with the following objectives: 1) To find out the form of traditional clothing and behavior in the Nyongkolan culture in Keruak District, 2) To find out the Islamic view of traditional clothing and behavior in the Nyongkolan culture in Keruak District. The type of research used is descriptive qualitative research, namely research that seeks to describe, record, analyze and interpret the conditions that currently occur or exist. The results of the study can be concluded that from the point of view of Islamic law the implementation of the nyongkolan culture is permissible, because nyongkolan is a form of implementation of the Prophet's hadith to announce marriage, where the marriage must be accompanied by music and singing. However, in the implementation of nyongkolan, there is another tradition in it, namely in terms of dress procedures which tend to be open and that violates the Shari'a theorems of syara'. Meanwhile, in terms of behavior, for example ngibing (dancing excessively) and drinking alcohol, it is destructive and cannot be made into a good tradition that cannot be accepted by religion. Because in the Qur'an it has been explained how to dress and behave in accordance with Islamic law. So the form of clothing used in the traditional nyongkolan procession must be in accordance with Islamic law, which is closed, especially for women who are required to cover their genitals from head to toe (entire body) except for the face and palms, by combining traditional clothing with cufflinks and hijab. And for men, they are required to cover their genitals from the navel to their knees, by wearing appropriate or appropriate traditional clothes as long as their genitals are covered. Meanwhile, in terms of behavior, it must also be in accordance with Islamic law, namely by following the good example of the great prophet Muhammad SAW, and always behaving well, appropriately, and not excessively.